Validação de sistema sindrômico multiplex para diagnóstico molecular de meningites bacterianas - Evangelista, Patricia Salles Estrela (2021)
It is estimated that anually there are more than 1.2 million cases of bacterial meningitis worldwide, with coefficients of incidence and lethality that vary according to region, country, age group and etiologic agent. In Brazil, the number of cases referring to bacterial meningitis is worrying, because besides its rapid evolution and lethality, it represents, in number of cases, the second largest number of records, with a representativeness of 27.4% according to the epidemiological surveillance data. Also, considering that the etiological identification and early diagnosis are essential for the definition of appropriate antimicrobial treatments, institution of control measures and monitoring of the disease’s epidemiological profile, along with the fact that during the bibliographic search an ordinary amount of fully automated platforms available on the market were found and a lack of compatibility between platforms and multiplex molecular panels was identified. The present study aimed to validate the multiplex molecular panel XGEN MULTI MB (Fab.: Mobius LifeScience, Ref. XG-MB-MB-24) for the use with a fully automated platform BD MAX™ System (Fab.: BD Diagnostics, Ref. BD MAX ™ System), forming together a multiplex syndromic system used for the molecular diagnosis of bacterial meningitis, later described as SSM MB. As validation layout, six stages of analytical tests were considered, including tests of robustness, analytical sensitivity, analytical specificity, precision, and accuracy, summing a total of 162 tests performed. For the testing procedure, previously known negative samples for the pathogens under analysis were used, along with synthetic standards of known concentration specific for the targets’ detection of the multiplex molecular panel XGEN MULTI MB. After the result’s evaluation, it was verified that the SSM MB multiplex syndromic system presented: amplification curves on exponential format, valid detection results and fluorescence values according to the pattern observed in the routine when using a gain of 80 (robustness tests); ability to detect Neisseria meningitidis, Streptococcus pneumoniae, and Haemophilus influenzae at a minimum concentration of approximately 13 copies/µL (analytical sensitivity tests); ability to perform detections only from the target pathogen, on specific channels and without evidence of fluorescence interference on anoother optical channels (analytical specificity tests); ability to detect successive measurements of the same analyte, under unaltered operating conditions and under different operating conditions, with consistent results and within the proposed acceptance criteria (precision tests); ability to detect measurement values, close to results accepted as truly correct (accuracy tests). Threfore, it was concluded that the SSM MB multiplex syndromic system met the objectives previously proposed with results considered satisfactory in all the tests performed. Such as that later, the data generated on this study will also be used by the manufacturer to update the product registration, adding the BD MAX™ System platform (Fab.: BD Diagnostics, Ref. BD MAX™ System) as an equipment compatible with the kit, at the correspondent regulatory authorities (ANVISA).